2015
DOI: 10.3109/0886022x.2015.1033608
|View full text |Cite
|
Sign up to set email alerts
|

Association of kidney and cysts dimensions with anthropometric and biochemical parameters in patients with ADPKD

Abstract: The aim of the study was to evaluate an association between kidney and cyst dimensions and anthropometric, clinical and biochemical parameters of autosomal dominant polycystic kidney disease (ADPKD) patients. Forty-nine adults, ADPKD-diagnosed patients aged 36 ± 11 years, and 50 healthy controls were included in the study. Oral glucose tolerance test (OGTT with 75 g of glucose) was performed and venous blood was collected to measure biochemical parameters and various ion concentrations. Ultrasound abdominal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…4 One study in adult patients with ADPKD has found significantly lower concentrations of magnesaemia. 16 However, the authors did not give information about the prevalence of hypomagnesaemia. Furthermore, they included also patients with diuretics -a drug that is known to cause hypomagnesaemia; 5 therefore, lower concentrations of magnesaemia due to diuretic therapy cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…4 One study in adult patients with ADPKD has found significantly lower concentrations of magnesaemia. 16 However, the authors did not give information about the prevalence of hypomagnesaemia. Furthermore, they included also patients with diuretics -a drug that is known to cause hypomagnesaemia; 5 therefore, lower concentrations of magnesaemia due to diuretic therapy cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the ADPKD patients has mutations in PKD1 or PKD2 , which encode polycystin‐1 (PC1) and polycystin‐2 (PC2), respectively (Cornec‐Le Gall et al., 2018 ). Although the exact prevalence is unknown, case reports indicate that ADPKD patients may also present with electrolyte abnormalities, including hypomagnesemia and hypo‐ or hypercalcemia (Pietrzak‐Nowacka et al., 2013 , 2015 ; Veeramuthumari & Isabel, 2013 ). However, the mechanism underlying the hypomagnesemia and hypocalcemia in APDKD remains elusive and is complicated by the fact that patients may be treated with different types of drugs, including diuretics against hypertension (Wuthrich et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In advanced ADPKD, hypertension is common and glomerular filtration rate (GFR) is reduced (6,48). Electrolyte disturbances in ADPKD are described in literature, but these reports are mostly restricted to cystic ADPKD (4,11,13,34,39,40,43,44,47,51,55,57,58). When electrolyte imbalances are detected in cystic ADPKD, it is not possible to discern whether these disturbances are caused by dysfunctional PC1 or by cyst formation or defects in GFR, which dramatically impair renal fluid flow and blood filtration, respectively.…”
Section: Introductionmentioning
confidence: 99%